1973
DOI: 10.3382/ps.0521722
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Its Genetic Variation and Co-Variation with Certain Economic Traits in Egg Type Chickens

Abstract: Indirect systolic blood pressures were measured on females of three egg type strains of chickens over five consecutive generations. The measurements were taken between 165-175 days of age. Blood pressure measurements were also taken in one generation on breeder males at 380 days of age. Two of the strains were under selection for egg production traits while the third strain was a control derived from the same genetic base as one of the selected strains. Mean blood pressures were 148 mm. Hg for females and 203 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In more recent studies, Sturkie (1970a,b) reported no association between blood pressure level and mortality, and this was particularly true when total mortality was low. Hollands and Merritt (1973) have shown higher mortality in some strains with lower than average blood pressure but no relationship in other strains. These results suggested that the differences in viability might be related to general level of mortality and that birds with higher than average blood pressure were better able to withstand greater dis- Blood Pressure ease exposure and physical stresses.…”
Section: Effects Of Blood Pressure Level On Mortalitymentioning
confidence: 95%
See 1 more Smart Citation
“…In more recent studies, Sturkie (1970a,b) reported no association between blood pressure level and mortality, and this was particularly true when total mortality was low. Hollands and Merritt (1973) have shown higher mortality in some strains with lower than average blood pressure but no relationship in other strains. These results suggested that the differences in viability might be related to general level of mortality and that birds with higher than average blood pressure were better able to withstand greater dis- Blood Pressure ease exposure and physical stresses.…”
Section: Effects Of Blood Pressure Level On Mortalitymentioning
confidence: 95%
“…In that study most of the change was in a hypertensive line and no random line was available for comparison. Hollands and Merritt (1973), who selected chickens for blood pressure in three strains over a 5-year period, reported combined heritabilities of 26-27%. Heart and Circulation: Anatomy, Hemodynamics, Blood Pressure, Blood Flow, and Body Fluids and hypotensive males, respectively, compared to 45 and 33% for the females.…”
Section: Effects Of Blood Pressure Level On Mortalitymentioning
confidence: 99%
“…Genetic parameters have also recently become available for a variety of different traits, e.g. cholesterol content of egg yolk (Cunningham et a/., 1974; Washburn and Nix, 1974;Becker et al, 1975Becker et al, , 1977Nahil eta/., 1977); plasma cholesterol level (Hollands and Merritt, 1973a;Marks and Siegel, 1977;Nahil et al, 1977); egg mass (Jain, 1972); egg yolk and albumen characters (Jain, 1972;Rodda et al, 1977); differences between the sexes in body weight (Ayoub and MCrat, 1973;Ayoub and Magraby, 1975); 4-week body weight in quail at different nutrition levels (Marks, 1973); blood pressure in layers (Hollands and Merritt, 1973b); intra-clutch oviposition interval (Foster, 1972(Foster, , 1973McClung, Wang and Jones, 1975;Yoo, Sheldon and Podger, 1976); ability of quail to utilise lysine (Godfrey, 1968); serum alkaline phosphatase level (Wilcox el al., 1962).…”
Section: (Ii) Quantitative Geneticsmentioning
confidence: 99%
“…Marks and Washburn (1977), Washburn and Marks, (1977)-selection for changes in egg yolk cholesterol content; Hollands and Merritt (1973a)-selection for changes in plasma cholesterol level; Godfrey (1968)-selection for lysine utilisation in quail; Hollands and Merritt (1973b)-Blood pressure in selected lines of layers; McClung et al, (1971) and Wilcox (1966)-selection for high level of serum alkaline phosphatase; Lerner and Bird (1948)-selection for resistance to riboflavin deficiency; Siege1 (1972)-selection for high and low mating frequency; Stino and Washburn (1973)-selection for high and low packed erythrocyte volume under adequate and stress environments; Nesheim (1969)-selection for high and low nicotinic acid requirement.…”
Section: (Ii) Quantitative Geneticsmentioning
confidence: 99%